Peran Teknologi Informasi Dalam Transformasi Persuratan Organisasi Di Era Digital Di MTS Insan Cita Medan - Tengku Darmansah; Ahmad Rifa’i; Indah Mayasari; Anti Annisa; Aisyah Oktaviana (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
In the digital era, information technology plays a vital role in transforming organizational correspondence systems. Implementation of this technology increases efficiency, reduces operational costs, and strengthens information security. Electronic mailing systems replace traditional paper-based methods with digital solutions such as email, document management, and collaboration platforms, which speed up and structure communication. Information technology also supports data integration, document tracking, and better accessibility, thereby increasing organizational productivity and responsiveness. However, the adoption of this technology faces challenges such as the need for adequate technological infrastructure, employee training, and management of organizational culture change. This research discusses the benefits and challenges faced in adopting information technology for correspondence transformation, as well as strategies for optimizing the digitalization process.